The Rulings of Homosexuality and its Effects on Society from the Perspective of the Islamic law - Saraa Najm Aldiyn Abd Alrazaaq; Luqman Hassan Abdullah (Islamic Sciences Journal, 2025)
Homosexuality is one of the behavioral phenomena that humanity has been affected with since ancient times. The Glorious Qur’an referred to this issue through the story of the people of Lot and their immoral actions. Over time, this phenomenon has fluctuated in prevalence, but it has been significantly increased in the modern era due to several factors, including the development of communication technologies and the efforts of some international organizations and Western countries to legalize homosexuality, permit same-sex marriage, and protect homosexual rights. Given the impact of these developments on Islamic societies, this study aims to clarify the Islamic rulings on homosexuality from a legal and objectives-based perspective that aligns with human nature — a central concern of Islamic law. The research addresses the legal foundations of these rulings through Qur’anic and Prophetic texts, reviews the opinions of scholars and Islamic schools of thought, and analyzes the psychological and social effects of this phenomenon on individuals and society. The study adopts both inductive and analytical methodologies to highlight the Islamic legal objectives (maqāṣid al-sharīʿah) behind the prohibition of homosexuality- particularly the preservation of lineage, morality, and social stability